Improvement of the State Water Cadastre’s Management System - L.T.Ibragimov; U.A.Raximov; Z.R.Yarkulov; J.U.Ortiqov (Research Parks Publishers, 2022)
The challenges of monitoring state water objects and creating a database based on geographic information systems for the upkeep of the state water cadastre are taken into consideration in this article. On how to enhance the state water cadastre systems, a decision is made.